2012
DOI: 10.1186/1471-2407-12-618
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of HLA-G promoter methylation status, HPV infection and cervical neoplasia in Curitiba, Brazil: a pilot analysis

Abstract: BackgroundThe causal association between persistent human papillomavirus (HPV) infection and cervical cancer has been established, but the mechanisms that favor HPV persistence in cervical cells are still unknown. The diminished capability of the immune system to control and resolve HPV infection is one of several hypotheses. The tolerogenic protein HLA-G has shown aberrant expression in a variety of cancers, which has been suggested as a mechanism for tumor escape from immunosurveillance. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…These results are in agreement with the low levels of HLA-G5 expression in cervical cancer ( 136 ). On the other hand, two researches recognized HLA-G 14bp DEL allele and + 3142C as associated with increased risk of cervical cancer ( 137 , 138 ), in agreement with increased expression of HLA-G in cervical cancer tissues ( 139 ) and with the spontaneous de-methylation of HLA-G promoter that allows immune-evasion and the development of precancerous cervical lesions ( 140 ). HLA-G has been also implicated in nasal polyposis development in the presence of HPV infection ( 141 ).…”
Section: Hla-g Impact In Viral Infectionsmentioning
confidence: 73%
“…These results are in agreement with the low levels of HLA-G5 expression in cervical cancer ( 136 ). On the other hand, two researches recognized HLA-G 14bp DEL allele and + 3142C as associated with increased risk of cervical cancer ( 137 , 138 ), in agreement with increased expression of HLA-G in cervical cancer tissues ( 139 ) and with the spontaneous de-methylation of HLA-G promoter that allows immune-evasion and the development of precancerous cervical lesions ( 140 ). HLA-G has been also implicated in nasal polyposis development in the presence of HPV infection ( 141 ).…”
Section: Hla-g Impact In Viral Infectionsmentioning
confidence: 73%
“…15 To our knowledge, the present study is the first to explore Many studies have discussed the role of HLA-G and IL-17 in various types of cancer. 16,20 However, this is the first study …”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the role of genetic factors in HPV infections and the carcinogenic process was provided by studies that showed an association with specific HLA-G coding region polymorphisms (96)(97)(98)(99)(100)(101)(102)(103)(104). Among the Canadian population, the HLA-G * 01:01:02 and HLA-G * 01:03 alleles were found to be related to an increased risk of HPV16 infection and persistent infections (96), while the HLA-G * 01:01:03 and HLA-G * 01:01:05 alleles were identified as significant predictors of cumulative coinfections over the follow-up period (97).…”
Section: Hla-g Polymorphisms In the Context Of Hpv Infectionsmentioning
confidence: 99%